Composite crystallization fouling characteristics of normal solubility salt in double-pipe heat exchanger. (August 2020) - Lv, Yang; Lu, Kai; Ren, Yongsheng
Highlights: Crystallization fouling of mixed salt in double-pipe heat exchanger is studied. Na2 SO4 is the main fouling substance in mixed salts. Rf is determined by Na2 SO4 content and heat transfer temperature difference. Crystallization fouling of mixed salt is controlled by chemical kinetics. NaCl decreases fouling thermal resistance and fouling rate. Abstract: The fouling behavior of normal solubility pure salt (Na2 SO4 ) and mixed salt (Na2 SO4 and NaCl) in counter-current double-pipe heat exchanger was investigated. Through real-time monitoring of inlet and outlet temperatures of hot and cold fluids, the influences of various factors such as the inlet temperature, inlet velocity of hot solution and solute mass ratio on the fouling thermal resistance were determined. The results show that the fouling thermal resistance is determined by the sodium sulfate content at the experimental temperature and the change of the solubility of sodium sulfate within the temperature difference of heat transfer. With the increase of the inlet velocity of hot solution, the thermal resistance of fouling decreases gradually, indicating that the fouling process is controlled by chemical kinetics. In the fouling experiment of mixed salt solution, the main deposition material is sodium sulfate. Due to the common ion effect, sodium chloride greatly affects the saturated solubility of sodium sulfate, with the increase of the mass ratio of sodium chloride, the fouling thermal resistance and the fouling rate decreases gradually, and the time when the fouling thermal resistance reaches the asymptotic value is prolonged. The research results can provide theoretical guidance for scale inhibition of cooling surface of double-pipe heat exchanger in the treatment of wastewater containing sodium sulfate. Graphical abstract: Image, graphical abstract